2021
DOI: 10.31234/osf.io/mtprn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infants and toddlers leverage their understanding of action goals to evaluate agents who help others

Abstract: Although studies have found that infants prefer helpful individuals over unhelpful ones, the basis of such evaluations is unclear. If infants and toddlers, like adults, understand helping as fostering others’ goals, then their evaluations should depend on their ability to infer the goal of an agent in need of help. Here, 15-month-old toddlers and 8-month-old infants (n = 48) differentially evaluated acts of help, consistent with their developing understanding of means-end actions. In further experiments (n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Despite some failures to replicate these findings (Salvadori et al, 2015;Schlingloff et al, 2020), a meta-analysis of experiments probing early social evaluations found that infants and toddlers demonstrate a significant preference for prosocial over antisocial agents (Margoni & Surian, 2018). Since this meta-analysis, 13 additional studies have provided evidence that infants and toddlers evaluate agents based on their social actions (see Woo et al, 2022), consistent with the hypothesis that infants and toddlers prefer agents who help others to achieve their goals. Margoni and Shepperd (2020) have found, moreover, that the failed replications in this literature are consistent with the expected levels of error (i.e., false negatives) that occur when many samples are drawn from a population whose evaluations show a true preference for prosocial agents.…”
Section: Early Capacities For Evaluating Social Agentsmentioning
confidence: 61%
See 2 more Smart Citations
“…Despite some failures to replicate these findings (Salvadori et al, 2015;Schlingloff et al, 2020), a meta-analysis of experiments probing early social evaluations found that infants and toddlers demonstrate a significant preference for prosocial over antisocial agents (Margoni & Surian, 2018). Since this meta-analysis, 13 additional studies have provided evidence that infants and toddlers evaluate agents based on their social actions (see Woo et al, 2022), consistent with the hypothesis that infants and toddlers prefer agents who help others to achieve their goals. Margoni and Shepperd (2020) have found, moreover, that the failed replications in this literature are consistent with the expected levels of error (i.e., false negatives) that occur when many samples are drawn from a population whose evaluations show a true preference for prosocial agents.…”
Section: Early Capacities For Evaluating Social Agentsmentioning
confidence: 61%
“…In lab-based experiments, similar methods have been used to assess infants' and toddlers' evaluations of agents (Colomer et al, 2020;Geraci et al, 2022;Hamlin et al, 2010;Kinzler et al, 2007;Powell & Spelke, 2018), with findings that are consistent with those of studies using reaching measures. Research conducted via video conferencing has used this visual preference method to probe early social evaluations (in situations that do not involve false beliefs), and found that looking and reaching measures converge in infants and toddlers (Woo & Spelke, 2022) (as reviewed above). Other research has used visual preference methods to probe toddlers' understanding of emotion, replicating in-lab findings (Smith-Flores et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the agents had instead been absent, infants chose randomly between the agents. These findings have been conceptually replicated and extended in additional situations involving helping and hindering (Woo et al 2017;Woo & Spelke 2022a, 2022c.…”
Section: The Intentions Of Agents Who Engage In Morally Relevantmentioning
confidence: 65%
“…For instance, upon being exposed to an agent taking an object from a patient, infants interpret the agent's action as directed to acquiring a resource, without considering the action's consequences on the object's original possessor ; see also Yin at al., 2022). While adults likely solve this selection problem by applying their knowledge about prototypical goal states (i.e., outcomes that generate direct or derived rewards), this strategy may not be available to infants due to their limited goal repertoire (Liu, Brooks, & Spelke, 2019) and their still developing understanding of means-ends-relations (Woo & Spelke, 2020). This challenge is further compounded for second-order social goals, such as helping, insofar as these actions cannot be construed by a common reference to a single agent's utility (Hobbs & Spelke, 2015).…”
Section: Infants Possess the Mature Concept Of Helpingmentioning
confidence: 99%